معجم الألفاظ ذات الدلالة الاجتماعية في كتابي"البيان والتبيين" و"الحيوان - Muflihah Muflihah (OKARA: Jurnal Bahasa dan Sastra, 2017)
The Arabic language can be viewed as individual phenomenon and social phenomenon. As individual phenomenon, language is considered as special identity of human. It is human specific because only human who has the ability to do verbal language. As for social phenomenon, language is a convention of society as the owner and user of that language. Therefore, in Arabic language, there are some mu’jam such as mu’jam alfadz which has related meaning to the society including lafad (word) which is associated with the meaning of social, political, economic, knowledge and etc. This research tried to study about types of mu’jam alfadz that have meaning that is related to the society comprehensively and in detail, hopefully, it can give integrative understanding especially for Arabic language teachers.